CLINICAS HOSPITAL (HOSPITAL DE CLINICAS DE PORTO ALEGRE) PUBLIC HEALTH NURSING SERVICE: 40 YEARS OF HISTORY - Heldt, Elizeth (Revista Gaúcha de Enfermagem, 2013)
The Public Health Nursing Service (SESP) of Clinicas Hospital (HCPA) celebrated its 40th anniversary in 2012 and was a pioneer in implementing outpatient nursing consultation. SESP was organized taking into consideration infrastructure to plan nursing care based on the policy in effect and the needs of the community(1). At that time, it was a huge challenge, since there were few models for outpatient nursing care. Therefore, the proposal was to make care dynamic and focused on self-care, modifying the traditional outpatient(1) nursing patterns. Thus, SESP was organized as a Service instead of a unit, specifically to make the creation of Programs(1) possible. It is necessary to recognize the actions of people who occupied strategic positions and established benchmarks. In 1972, the first chief was a professor at the Federal University of Rio Grande Sul Nursing School (EENF/UFRGS), Lea Cecilia Muxfeldt, who, in a pioneering move in conjunction with coordinator, Professor Maria Helena Nery, initiated SESP’s activities. The following nurses were also part of this project: Arlete Spencer Vanzin, in the area of Adult Health Nursing; Baltazar Renosi Lápis, in the area of Psychiatric Nursing; Nilcéa Maria Nery Duarte, in the area of Obstetrical Nursing; Lourdes Falavigna Boeira and Walderez Spencer Uebel, both in the area of Puericulture(2) Nursing. During the 70s and 80s, the objectives of SESP were planning, organizing and coordinating HCPA public health programs, including health promotion through self-care geared towards patients and their families; and working as a teaching and research center for public health nursing. Nurses carried out activities related to individual and group care for patients and their families; technical and administrative activities related to continued education; supervision of the nursing team; organization, implementation and assessment of programs, as well as teaching and research activities together with the multidisciplinary and faculty team from EENF/UFRGS(1,2). Since its implementation in 1972, nursing consultation has employed phases of the nursing process, based on the Theory of the Basic Human Needs by Wanda Horta. Its main focus is on individual health(1) needs. It is important to note that SESP’s pioneerism in Brazil was directly related to the implementation of nursing consultation as an independent activity offered by nursing professionals to the community(1,2) systematically and continuously. This initiative influenced the regulation of the Professional Practice Law of 1986, establishing nursing consultation as a private activity of the nurses(3). Adapting to the evolution of the Health System, the programs were expanded and adapted, including the configuration of SESP, which has been modified over the years. The current configuration of the HCPA Nursing Group flowcharts has been in effect since January 2009, with SESP comprised of 15 outpatient zones and the Basic Health Unit (UBS). The team is composed of nurses, nursing technicians and assistants. The professors of EENF/UFRGS and the chief nurses of HCPA(4) unit board oversee the management. Currently, SESP maintains actions targeted at the primary (UBS), secondary and tertiary (outpatient) health-focused levels, integrated to the reference and counter-reference of the Unified Health System (SUS). Care related activities are developed through nursing consultations, educational groups, home visits and specific procedures. These are the Health Programs: Children’s, Women’s, Adult and Elderly, Mental Health and Basic Care. Access to consultations is based on SUS’s principles, referrals by professionals of the institution, and according to the specificity of each program. The quest to qualify care has been occurring, grounded on the scientific method of Systematization of Nursing Care (SAE), with NANDA-I(2) taxonomy as the theoretical benchmark for Nursing Diagnosis (DE). Over the last few years, SESP has been important in the development of undergraduate and graduate education, as well as research, focused on clinical interventions for outpatient care. Considering the interest of the nursing team responsible for this Service and, based on countless research questions that emerge from this practice, the Outpatient Nursing and Basic Care Research Group – GPEAMAB(4) – was created and registered in the directory of the CNPq (National Council for Scientific and Technological Development). The results of these three studies were published in the Revista Gaúcha de Enfermagem, one in the current issue and the other two in the subsequent editions. The systemized record of nursing history is relevant in undxerstanding who we are today in this profession and as professionals. Within a political and social context, the collective memory is also formed by routine actions, fostering the construction of a professional identity. SESP’s trajectory is characterized by the constant pursuit for adapting to the public policies in effect and the institutional objectives. The nursing team is motivated and aware of the change process aimed at boosting patient care flow, maintaining the quality characteristic of these 40 years of history.